An isolated pulmonary nodule secondary to Streptococcus intermedius infection in an otherwise healthy 10-year-old boy: A case report and literature review - Huang, Meixia; Li, Shuxian; Wu, Xiling; Xu, Dan; Tang, Lanfang; Chen, Zhimin (Frontiers in Pediatrics, 2022)
Streptococcus intermedius, as a Gram-positive commensal bacterium, has the tendency to cause various infections, such as brain and liver abscesses, endocarditis, and empyema, especially in immunocompromised patients. However, an isolated pulmonary nodule caused by S. intermedius in previously healthy individuals without traditional risk factors is rarely reported. Herein, we present a case of ten-year-old immunocompetent boy referred to our department with a 5-day history of intermittent, left sided chest pain. Chest X-ray and computed tomography revealed a left lung nodule. Although his blood, sputum and bronchoalveolar lavage fluid cultures were negative, metagenomic next-generation sequencing (mNGS) showed only the presence of S. intermedius in ultrasonography-guided lung biopsy tissue and pleural fluid (416 and 110 reads, respectively). He was then successfully treated with appropriate intravenous antibiotics and avoided surgical intervention. To our knowledge, this is the first report of S. intermedius related pulmonary nodule confirmed by mNGS analysis in healthy children. For achieving proper diagnosis and treatment, infection with S. intermedius should be included in the differential diagnosis when coming across such a similar pulmonary nodule. mNGS, as a valuable supplement to conventional culture methods, is an essential diagnostic tool for identifying pathogen without typical characteristics.